Mooraboolomyces wintlei gen. & sp. nov. from Victoria, Australia - Hull, Caitlin P.; Urquhart, Andrew S.; Idnurm, Alexander (Phytotaxa, 2024)
A new genus and species in the Mucoromycota, Mooraboolomyces wintlei, was isolated into culture from leaf litter from a national park in Victoria, Australia, and is described. The strain reproduced asexually to form sporangia and sporangiospores, with no production of zygospores, and sequencing of its genome and analysis supported a heterothallic mode of reproduction. Phylogenetic analyses using five DNA regions placed the strain within the Mucorales and Mucoraceae, clearly distinct from previously described genera. This represents the second genus in this phylum that has been identified from Australia and that is currently unique to this country.